The Role of Specialized Courts in Developing the Judicial System (Comprehensive Journal of Science, 2026)
This study aims to demonstrate the role of specialized courts in developing the judicial system by enhancing the efficiency of judges and expediting the resolution of disputes of a technical and economic nature. It also highlights their impact on improving the quality of judgments, strengthening public trust in the judiciary, and supporting the investment climate. The central issue revolves around the effectiveness of implementing specialized courts considering the challenges related to judicial unity and fair trial guarantees. A comparative analytical approach was adopted to examine the legislation and comparative experiences. The results indicated that specialized courts contribute to reducing litigation delays, improving the quality of judicial reasoning, unifying legal interpretations, and supporting the judiciary in keeping pace with technological and economic developments and enhancing the investment climate. The results also showed that comparative experiences confirm the effectiveness of this system in improving judicial performance                                                                                                      The study recommended the gradual adoption of specialized judiciary through the establishment of specialized circuits within existing courts, the development of the legislative framework regulating it, the qualification and training of judges, the strengthening of the digital infrastructure of the judiciary, in addition to benefiting from comparative experiences in a manner that is compatible with national particularities
Keywords: Judicial System, Development, Legislation, Specialized Courts